KERAGAMAN JENIS BURUNG AIR DI TAMAN NASIONAL WASUR, MERAUKE - Aji Winara (Lambung Mangkurat University-Indonesia, 2016)
Water birds is one of the featured biodiversity of Wasur National Park in Papua. Rawa Donggamit and Ndalir Beach is a habitat for water birds closest to residential areas and became the object of tourist attraction. This study aims to determine the species diversity of water birds and habitat conditions in Wasur National Park. The research was conducted in October 2010. The method was used is the exploration field. The results showed as many as 56 species of birds from 15 families found scattered in the area of Rawa Donggamit (50 species) and Ndalir Beach (22 species). The diversity level of bird classified as moderate with Shannon-Wienner value index (H ') of 1,72 to 2,81, Margalef richness index (R') is high for Rawa Donggamit (R '= 6,32) and moderate for Ndalir Beach (R '= 2,64). There are significant differences in the diversity between locations with Jaccard index value of 0,28. The condition of the habitat of water birds in the Rawa Donggamit suffered invasion some plant species with the widest level of invasion is kind of Fimbristylis sp. 25% of the forest habitat, while bird habitat in Ndalir beach was not much disturbed.Burung air merupakan salah satu keanekaragaman hayati unggulan di Taman Nasional Wasur Papua. Rawa Donggamit dan Pantai Ndalir merupakan habitat burung air terdekat dengan wilayah pemukiman dan menjadi objek daya tarik wisata. Penelitian ini bertujuan untuk mengetahui keragaman jenis burung air dan kondisi habitatnya di Taman Nasional Wasur. Penelitian dilaksanakan pada bulan Oktober 2010. Metode penelitian yang digunakan adalah penjelajahan lapangan. Hasil penelitian menunjukkan sebanyak 56 jenis burung dari 15 famili dijumpai tersebar di wilayah Rawa Donggamit (50 jenis) dan Pantai Ndalir (22 jenis). Tingkat keragaman jenis burung tergolong sedang dengan nilai indeks Shannon-Wienner (H’) sebesar 1,72-2,81, Indeks kekayaan Margalef (R’) tergolong tinggi untuk Rawa Donggamit (R’= 6,32) dan sedang untuk Pantai Ndalir (R’= 2,64). Terdapat perbedaan keragaman yang nyata antar lokasi dengan nilai Indeks Jaccard sebesar 0,28. Kondisi habitat burung air di Rawa Donggamit mengalami invasi beberapa jenis tumbuhan dengan tingkat invasi terluas adalah jenis Fimbristylis sp. mencapai 25 % dari luas habitat, sedangkan habitat burung di Pantai Ndalir tidak banyak terganggu.